2020
DOI: 10.18502/ijph.v48i7.2941
|View full text |Cite
|
Sign up to set email alerts
|

Medical Tourism in Iran, Reevaluation on the New Trends: A Narrative Review

Abstract: Background: This narrative review aimed to reevaluate the medical tourism sector in Iran to reveal the new trends and activities in order to know the current actual share of Iran in the competitive market of global medical tourism. Methods: A holistic approach was adopted to analyze the information collected through a system of investigation that comprised the available secondary data, besides the information and statistical data about the associated organizations to this sector in Iran. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…The number of patients has increased continuously and now the Korean medical tourism industry aims to attract 800,000 foreign patients by 2020. While there have been improvements in the growth of the industry, the needs of patients from various countries and culture have been diversified and their standards on the quality of medical tourism have been increased, that roots in the cultural and family preferences (25, 26).…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients has increased continuously and now the Korean medical tourism industry aims to attract 800,000 foreign patients by 2020. While there have been improvements in the growth of the industry, the needs of patients from various countries and culture have been diversified and their standards on the quality of medical tourism have been increased, that roots in the cultural and family preferences (25, 26).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, sanctions have also affected Iran's prominence in medical tourism in the region, so that while Iran had the potential to earn $7 billion annually, this has been reduced to less than $1 billion per year. 31 A more concerning issue is the brain drain from the sanctioned countries like Iran. Typically, when scientists find it too challenging to pursue science in their homeland, they migrate to resource-rich countries to continue their career trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible to improve the quality of services and satisfaction by engaging patients in the care process (25), only two websites clearly showed that feedback or suggestion mechanisms are used to assess medical tourists' views on services they required or had received. Previous research has shown that the existing medical tourism industry in Iran, including the associated ICT infrastructure and websites, has been underdeveloped and is not practical enough to retain consumer interest (17,22,23). These studies argue that the use of such websites does not allow patients to survey their needs, opinions, or feedback.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Iran hosted 3.3 million tourists (14), most of whom sought medical treatment (15). Likewise, in the first seven months of 2018, over 4.7 million visitors arrived in Iran, of whom around 300,000, largely from Central Asian and Arab countries, were possibly attracted to the country's health care system (16,17). Given the above, it is reasonable to believe that Iran has an extremely large scope for medical tourism to grow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation